Implementación de un sistema de información geográfica para la optimización de las actividades comerciales de lectura y balance hídrico de una empresa de servicios públicos domiciliarios de acueducto (2022)
The provision of residential public services is an activity that is preserved over time. Regardless of the place, the topographical conditions, the cultures, etc., large human settlements (towns and cities) have always required and will require home public services; These “Are those that are provided in a universal, continuous, efficient, obligatory manner, in equal conditions and quality to all users, through physical or human networks in their place of residence or work, with a special legal regime of right public, with the direct participation of the Public Administration in its provision, regulation and control" (Matias Camargo, 2013).